"Japan's foreign aids policy to Africa" : the cases of Angola and Mozambique within the TICAD process - Carvalho, Pedro Miguel Raposo de Medeiros, 1969- (2011)
Lusíada. Economia & empresa. - ISSN 1645-6750. - S. 2, n.13 (2011). - p. 95-122.